Breeding Ecology of Birds at Teshekpuk Lake: A Key Habitat Site on the Arctic Coastal Plain of Alaska - Liebezeit, J.R.; White, G.C.; Zack, S. (ARCTIC, 2011)
The Teshekpuk Lake Special Area in the National Petroleum Reserve – Alaska (NPR-A) currently has no long-term protection from oil development. In this study, we provide novel information on nest density, productivity, and habitat use at Teshekpuk relative to a developed oilfield site at Prudhoe Bay, Alaska, to assess the importance of Teshekpuk for tundra-nesting birds and to provide recommendations regarding potential oil development. Mean annual nest density of all bird species combined was significantly higher at Teshekpuk than at Prudhoe Bay and was higher than any of five other sites with comparable data on the Alaskan Arctic Coastal Plain. Nest densities were significantly higher at Teshekpuk than at Prudhoe Bay for Lapland longspurs (Calcarius lapponicus) and long-billed dowitchers (Limnodromus scolopaceus), although those for semipalmated sandpipers (Calidris pusilla) were higher at Prudhoe Bay. Total shorebird nest densities at Teshekpuk were among the highest of any sites in the region. At Teshekpuk, shorebirds nested preferentially in wet and emergent habitats, including flooded low-center polygons, non-patterned tundra, and Carex aquatilis-dominated habitats. Therefore, we recommend that future oil infrastructure placement in this region avoid these habitats. Using data collected at Teshekpuk and Prudhoe Bay from 2005 to 2008, we modeled nest survivorship for 11 shorebird species and for Lapland longspurs. For longspurs, the best-supported models based on AICc values indicated that nest survival was always higher at Teshekpuk, but it was also higher elsewhere in years of high lemming abundance and later in the nesting season. For shorebirds, the best-supported models indicated that nest survivorship was highly variable among years and sites. Uniparental-nesting shorebirds had lower nest survivorship shortly after nest initiation followed by a rapid increase, while biparental survivorship was consistently high throughout the nest lifetime. We recommend that disturbances to nesting habitat be minimized ...